2002
DOI: 10.1128/jcm.40.10.3625-3630.2002
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Sequence Analysis of the Core Protein and Its Frameshift Product, the F Protein, of Hepatitis C Virus Subtype 1b Strains Obtained from Patients with and without Hepatocellular Carcinoma

Abstract: The core protein of hepatitis C virus (HCV) has been implicated in hepatocarcinogenesis. In order to determine whether there is a correlation between mutations of the core protein and the development of hepatocellular carcinoma (HCC), the core protein-coding sequence of the viral genome of HCV subtype 1b (HCV-1b) obtained from patients with and without HCC was analyzed. We found that 12 (40.0%) of 30 HCV-1b isolates from patients with HCC but none of 29 isolates from patients without HCC had a point mutation(s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
36
0
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 34 publications
5
36
0
4
Order By: Relevance
“…In line with previously reported data, compartmentalization was observed consistently in tumoral hepatocytes. 25,27,29,30 Our results also showed that HCV replication is less efficient in tumoral hepatocytes and that HCC quasispecies are subjected to weak selective pressure, exhibiting stronger diversity and entropy than those derived from nontumoral tissues. Also, we demonstrated the compartmentalization of HCV core quasispecies between 2 cirrhotic nodules.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…In line with previously reported data, compartmentalization was observed consistently in tumoral hepatocytes. 25,27,29,30 Our results also showed that HCV replication is less efficient in tumoral hepatocytes and that HCC quasispecies are subjected to weak selective pressure, exhibiting stronger diversity and entropy than those derived from nontumoral tissues. Also, we demonstrated the compartmentalization of HCV core quasispecies between 2 cirrhotic nodules.…”
Section: Discussionsupporting
confidence: 50%
“…[22][23][24] The distribution of liver quasispecies may also differ when HCC and nontumoral cirrhotic liver are compared. [25][26][27][28][29][30] Finally, some articles have shown that peripheral blood mononuclear cells or hepatic lymph nodes can harbor minor or major variants not found in the serum. 31,32 However, in none of these studies was serum, different parts of the liver, and HCC from the same subjects examined.…”
mentioning
confidence: 99%
“…In addition, phylogenetic analysis with the core11 amino-acid sequence has shown that the core11 variants obtained from HCC samples differ from those in nontumor cells, consistent with the selection of core11 variants with modified functional properties in HCV-induced HCC. Previous studies also reported the accumulation of characteristic mutations in specific regions of the HCV core/core11 RNA sequence in patients with HCC, these mutations being associated with an increase in the production of alternative forms of core/core11 proteins in cell-free systems in several cases (46)(47)(48)(49)(50)(51).…”
Section: Evidence For Core11 Protein Production During Natural Hcv Inmentioning
confidence: 99%
“…The length of the core11 protein appears to be genotype-specific, varying between 126 and 162 amino acids (162 aa for genotype 1a, 144 aa for 1b, 126 aa for 2a, and 126-155 amino acids for most of the sequences of other genotypes) (19). The core11 amino-acid sequence displays a lower level of conservation than the core protein (50,54,55), but is at least as well conserved as the E1 and NS2 HCV proteins encoded by the main ORF (55). Similar results were obtained in both conventional homology analysis, in which proteins encoded by diverse HCV RNA sequences are compared in pairs to determine the percentage of identical amino acids, and with a new package of data mining tools (Mutation Master) comparing individual sequences in a multiple alignment with a reference sequence (consensus sequence constructed to correct for the overrepresentation of certain genotypes) at each amino acid position.…”
Section: Conservation Of the Core11 Orf/protein Among Hcv Isolatesmentioning
confidence: 99%
“…These studies suggest a link between coreϩ1/ARFP and development of liver cancer (22)(23)(24)(25)(26)(27). Conversely, coreϩ1/ARFP has no obvious effect on virus replication following electroporation of Huh7-Lunet cells with fulllength JFH1 wild-type and mutated viral RNAs or in mice xenografted with human liver tissue (28).…”
mentioning
confidence: 99%